2019
DOI: 10.26599/bsa.2019.9050025
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the hippocampus in chronic pain and depression

Abstract: Increases in depressive behaviors have been reported in patients experiencing chronic pain. In these patients, the symptoms of pain and depression commonly coexist, impairing their lives and challenging effective treatment. The hippocampus may play a role in both chronic pain and depression. A reduction in the volume of the hippocampus is related to reduced neurogenesis and neuroplasticity in cases of chronic pain and depression. Moreover, an increase of proinflammatory factors and a reduction of neurotrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 93 publications
1
40
0
Order By: Relevance
“…Depression is an alteration in cognitive behavior and mood, featured by cognitive dysfunction, pleasure loss, negative mood, social isolation fatigue, sleep disorders, appetite loss, and other metabolic changes [2,3]. Among different regions of the brain, it has been shown that reduced volume of the hippocampus is strongly correlated with the severity of depression [4] Long-term unpredicted and repeated stress triggers a cascade of in ammatory responses in the brain [5]. A growing body of evidence from preclinical and clinical studies indicates that he depression is attributed to the higher levels of cytokines, such as interleukin (IL)-6, IL-1β in blood and cerebrospinal uid [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is an alteration in cognitive behavior and mood, featured by cognitive dysfunction, pleasure loss, negative mood, social isolation fatigue, sleep disorders, appetite loss, and other metabolic changes [2,3]. Among different regions of the brain, it has been shown that reduced volume of the hippocampus is strongly correlated with the severity of depression [4] Long-term unpredicted and repeated stress triggers a cascade of in ammatory responses in the brain [5]. A growing body of evidence from preclinical and clinical studies indicates that he depression is attributed to the higher levels of cytokines, such as interleukin (IL)-6, IL-1β in blood and cerebrospinal uid [6].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the elevated levels of in ammatory cytokines such as tumor necrosis factor-alpha (TNF-α), IL-1β, and IL-6 in brain regions, including the hypothalamus, hippocampus, and/or prefrontal cortex, have been reported following depression [7,4]. The nucleotide-binding domain, leucine-rich repeat (NLR) pyrin domain protein 3 (NLRP3) in ammasomes, an intracellular multi-protein complex, is activated in various neurological and psychological disorders [8].…”
Section: Introductionmentioning
confidence: 99%
“…Depression is an alteration in cognitive behavior and mood, featured by cognitive dysfunction, pleasure loss, negative mood, social isolation fatigue, sleep disorders, appetite loss, and other metabolic changes [2,3]. Among different regions of brain, it has been shown that reduced volume of hippocampus is strongly correlated with the severity of depression [4] Long-term unpredicted and repeated stress triggers a cascade of in ammatory responses in the brain [5].…”
Section: Introductionmentioning
confidence: 99%
“…Pain and emotion are closely related. From a theoretical perspective, pain can be defined as a type of unpleasant emotional experience and includes the feelings of depression and sadness (Mokhtari et al, 2019). Particularly, the motivational-affective dimension of pain is closely linked with emotion (Melzack and Casey, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…From a neuropsychological perspective, similar brain regions represent both pain and emotion. For example, the medial frontal cortex (including the anterior midcingulate cortex; Kragel et al, 2018 ), the midbrain periaqueductal gray ( Buhle et al, 2013 ), and the hippocampus ( Mokhtari et al, 2019 ) are involved in both pain and negative emotions, suggesting that the experience of pain influences the processing of negative emotions.…”
Section: Introductionmentioning
confidence: 99%